Menyeimbangkan Kepatuhan Syariah dan Tata Kelola: Mengevaluasi Beragam Peran Dewan Pengawas Syariah dalam Perbankan Syariah - Ilham Akbar, Bastaka; Fatma Laela, Sugiyarti (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2025)
The research explores the Sharia Supervisory Board's (SSB) role in Islamic banking governance, in on balancing Sharia compliance with effective governance. Using qualitative methods through document analysis and interviews, the study investigates how SSBs manage their various responsibilities including compliance oversight, product development, and auditing. The research found that SSBs significantly impact operational risk management and stakeholder confidence. Banks with strong Sharia governance frameworks show better compliance and risk management. Main challenges include expertise gaps, resource limitations, and regulatory complexity. The research emphasizes the importance of professional development, standardized reporting, and organizational integration of SSBs. It provides valuable insights for developing stronger governance structures in Islamic banking, offering implications for policymakers, practitioners, and scholars in the field. This study contributes to the broader understanding of corporate governance in Islamic finance, particularly in creating frameworks that balance both operational effectiveness and religious compliance.